Optimization of radiation dose for sacrum bone examination with AP, axial AP and axial PA projections - Indrati, Rini; Indrati, Rini; Kartikasari, Dewi; Kartikasari, Dewi; Mulyati, Sri (International Journal of Psychosocial Rehabilitation, 2020)
Sacrum bone examination projection is Anteroposterior axial with CR 15o to the cephalad, the posterior-anterior axial with CR 15o caudal and lateral. Some practitioners take action to examine the sacrum bone with AP projections used the perpendicular beam. The radiation dose has a negative effect in the stochastic and deterministic. One factor in radiation dose is the distance between the source and the organ. The research aims to determine the projection that produces good information with minimal doses. This is an experimental study. Radiographs from AP, Axial AP and Axial PA projection assessed by the radiologist regarding the clarity of anatomic and the dosage was measured using TLD. Data analyzed by Friedman and Wilcoxon test with α = 5%.The results showed there were differences in anatomical information clarity radiographs on the AP, Axial AP and Axial PA projections with p-value = 0.001. The best information obtained on Axial PA projections. There are differences in radiation doses in the right ovary (p-value = 0.002), left ovary (p-value < 0.001) and Gonad (p-value < 0.001). The Axial PA projection produced the best information with a minimum dose.